Learning Disabilities - Neurobiology, Assessment, Clinical Features and Treatments 2022
DOI: 10.5772/intechopen.101511
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Learning Disability

Abstract: Learning disabilities (LDs) are caused by genetic and/or neurological factors that alter brain functioning and affect processes related to learning, which include dyslexia, dysgraphia, and dyscalculia. It hinders the child’s academic, social, and overall life skills. Current treatments for LD include medication and rehabilitation, focusing on management of symptoms. Thus, there is a need to explore newer treatments which will work at cellular level. Stem cell therapy is an evolving field of regenerative medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…29,30 Furthermore, these results are consistent with existing studies in which stem cell therapy has been shown to enhance various abilities in patients with autism spectrum disorder or cerebral palsy, including comprehensive skills, attention, reading, writing, and memory capabilities. 31 Numerous studies investigating the application of stem cell therapy in stroke patients have yielded promising outcomes. A study conducted by Lee et al 20 showed that patients who received stem cell therapy displayed notable improvements in motor function, as assessed using the Fugl-Meyer assessment system, within a 90-day evaluation period.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Furthermore, these results are consistent with existing studies in which stem cell therapy has been shown to enhance various abilities in patients with autism spectrum disorder or cerebral palsy, including comprehensive skills, attention, reading, writing, and memory capabilities. 31 Numerous studies investigating the application of stem cell therapy in stroke patients have yielded promising outcomes. A study conducted by Lee et al 20 showed that patients who received stem cell therapy displayed notable improvements in motor function, as assessed using the Fugl-Meyer assessment system, within a 90-day evaluation period.…”
Section: Discussionmentioning
confidence: 99%